The Effectiveness of Utilizing a Software Based on Spatial Intelligence Strategies in Developing Architectural Design Thinking Skills Among 11th-Grade Female Students - Al-Ghawi, Zouwaina Khalaf; Al-Najar, Noor Ahmed (Journal of Curriculum and Teaching Methodology, 2025)
The spatial intelligence strategy, in developing design thinking skills among 11th-grade female students. The students’ performance was assessed using a design thinking situations scale consisting of 15 scenarios distributed across five dimensions: empathy, problem identification, idea generation and visualization, prototype design, and testing. The researcher applied the scale to a sample of 68 students from Umm Al-Khair Basic Education School (Grades 10–12) in the Sultanate of Oman. The sample was divided into two groups: a control group of 35 students who studied architectural design examples through the traditional method, and an experimental group of 33 students who studied the same content using the Floor Plan Creator software. The study results revealed significant differences in the design thinking skills scale between the two groups. Moreover, the overall effect size of the Floor Plan Creator software on the level of design thinking performance was high in favor of the experimental group. Accordingly, the researcher recommended the importance of utilizing architecture-related software to enhance design thinking skills among school students in preparation for future competencies.
Keywords: Floor Plan Creator Software; spatial intelligence strategies; Design Thinking